Recovery of Titanium Resources from Spent SCR Denitration Catalysts - Yang PENG (Kuangchan zonghe liyong)
The waste catalysts of the flue gas purification system of thermal power plants contain valuable metals such as titanium, tungsten, molybdenum, vanadium, etc.. The recovery of valuable resources from them is a hot research topic at present. The main valuable resource in the SCR denitration catalyst used in this paper is TiO2. The chemical titration results show that the content is 70.18%, the main impurities and their contents are: Na2O content is 10.81%, SiO2 content is 5.06%, Al2O3 content is 0.95% , and Fe2O3 content is 0.47%. The particle size analysis of the sample shows that there is TiO2 distribution in each particle size, and there is no obvious aggregation phenomenon. In this paper, the combined process of sodium salt roasting, sulfuric acid leaching, and leaching residue calcination can remove most of the impurities and finally obtain a calcined product with a TiO2 content of 89.75%.